2007
DOI: 10.1002/pssc.200673346
|View full text |Cite
|
Sign up to set email alerts
|

Control of a double quantum dot structure by stimulated Raman adiabatic passage

Abstract: In this work we study the potential for coherent manipulation of an asymmetric double quantum dot structure by the use of adiabatic methods. These methods are the Stimulated Raman Adiabatic Passage (STIRAP) and its modification the fractional STIRAP. We show that such a method can be used for complete electron transfer between the two lower states of the quantum dots. In addition, with fractional STIRAP a coherent superposition of the two lower states of the quantum dots can be created.1 Introduction The inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…• coherent manipulation of an asymmetric double-QD structure (Voutsinas et al, 2007) and coherent electron transfer between the ground states of two coupled QDs (Fountoulakis and Paspalakis, 2013).…”
Section: Semiconductor Quantum Dotsmentioning
confidence: 99%
“…• coherent manipulation of an asymmetric double-QD structure (Voutsinas et al, 2007) and coherent electron transfer between the ground states of two coupled QDs (Fountoulakis and Paspalakis, 2013).…”
Section: Semiconductor Quantum Dotsmentioning
confidence: 99%
“…1. [29][30][31][32][33][34][35][36][37][38] The device is composed of two nonidentical quantum dots, marked as left (L) and right (R) dots, respectively. Usually, the coupled QD structures are described as a quasi-one-dimensional problem.…”
Section: Model Hamiltonian For Coupled Quantum Dotsmentioning
confidence: 99%
“…13 To date, the effect of time-varying external fields on electronic population transfer in semiconductor QD systems has attracted considerable attention and manifest some interesting effects ranging from photon-assisted tunneling to electron pumping. Many theoretical and experimental schemes for controlling transfer of one-electron or twoelectron in coupled QD system have been reported, [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40] and experimental methods to determine the interdot tunnel coupling both for ground and excited states have been developed. 23,24 As an example, stimulated Raman adiabatic passage (STIRAP) is a very popular method to produce completed population transfer in the quantum dot structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, an electron transfer between levels of identical quantum dots at one-photon resonance was considered in [1][2][3][4][5][6][7][8], and [9][10][11][12] treated transfer processes at a combinational and two-photon resonance between discrete levels of an electron system of two quantum dots with essentially different energies. In [13] the case is considered when the levels relating to two different but not necessary identical quantum dots possess approximately similar energy, and it was shown that the system is enough to be affected by electromagnetic field with only one carrier frequency for an electron transfer between quantum dots, and it is not obligatory for any resonance condition to be obeyed.…”
Section: Introductionmentioning
confidence: 99%